Sejarah Geologi dan Stratigrafi Batugamping Miosen Daerah Pakisrejo dan Sekitarnya, Kabupaten Tulungagung, Jawa Timur - Widada, Sugeng; Muttahari S., S.T., M.Sc., Moch. Prahastomi; Ansony, Muhammad A.N.; Rizky, Aga (Jurnal Ilmiah Geologi PANGEA, 2025)
The study area is geographically located in Pakisrejo, Tulungagung Regency, East Java Province, and physiographically in the Southern Mountain Zone of East Java. This research aims to investigate the stratigraphic framework, reconstruct the geological evolution, and interpret geological processes that facilitated the development of carbonate rock formations within the study area during the Oligocene to Miocene epochs. The field investigation involved the construction of detailed outcrop profiles, measurement of stratigraphic sections along representative traverses, and the systematic collection of rock samples for laboratory analysis. Subsequent laboratory investigations comprised petrographic analysis, aimed at determining mineralogical and textural characteristics, and paleontological analysis to identify fossil content and interpret paleoenvironmental conditions. The geological evolution of the area commenced during the Oligocene to Early Miocene, a period marked by significant magmatic activity that led to the emplacement of the Mandalika Volcanic Breccia Unit and the Andesite Intrusion Unit. Volcanic activity ceased during the Late Oligocene to Early Miocene, initiating a phase of erosion. This was followed by a marine transgression that facilitated the deposition of the Campurdarat Calcarenite Unit, the Campurdarat Reef Limestone Unit, and the Campurdarat Calcirudite Unit, indicating a transition to a shallow marine carbonate platform environment. A major tectonic uplift during the Late Middle Miocene terminated carbonate sedimentation and resulted in the emergence of the study area as subaerial land. The final phase of the geological history is characterized by denudational processes, which led to the development of the Alluvial Deposit Unit—a dynamic process that continues to shape the landscape to this day. The evolution and proliferation of Miocene carbonates in the study area were predominantly influenced by climatic conditions, paleotopography, and marine transgression dynamics, which collectively created favorable conditions for carbonate sedimentation and reef development.